Making choices for multicultural education : five approaches to race, class, and gender - Sleeter, Christine E., 1948-; Grant, Carl A. (Upper Saddle River, NJ : Merrill, 1999)
Illusions of progress. Teaching the exceptional and the culturally different. Human relations. Single-group studies. Multicultural education. Education that is multicultural and social reconstructionist.
Keywords: Education; United States; Multicultural education; Multiculturalism; Social classes; Multicultural education -- United States; Children of minorities -- Education -- United States; Social classes -- United States